An alternative retrograde access puncture for EVLA: a case report - Kurniawan, Catur Rizky; Kurnianingsih, Novi; Widito, Sasmojo (Universitas Brawijaya, 2025)
Background: CVI manifests with a variety of clinical symptoms, spanning from varicose veins to venous ulcers, significantly impacting patients' daily lives. While traditional treatments such as compression therapy and surgery remain options, on endovenous laser treatment (EVLT) has emerged as a viable alternative. This article delves into the management of CVI, with a particular focus EVLT as a minimally invasive intervention. Through two case illustrations, it sheds light on the difficulties encountered when accessing the great saphenous vein (GSV) using the conventional antegrade approach, particularly in cases involving obesity and vasospasm. Consequently, a retrograde EVLT technique utilizing proximal GSV access, resulting in successful vein ablation with minimal complications. Overall, this approach presents a promising addition to the management of CVI, offering enhanced patient care and improved outcomes. Case Presentation: Two patients with CVI and challenging antegrade GSV access underwent retrograde EVLT using proximal GSV access. Despite initial difficulties, including obesity and vasospasm, successful vein ablation was achieved with minimal complications. Post-procedural evaluations demonstrated significant symptomatic improvement, highlighting the efficacy of the retrograde technique. Conclusion: Retrograde EVLT utilizing proximal GSV access proves to be a safe and effective alternative in cases where antegrade access is challenging. The technique offers simplicity, minimal complications, and high patient satisfaction, with outcomes comparable to traditional approaches. Extended follow-up studies are needed to confirm the long-term effectiveness of retrograde EVLT compared to antegrade methods. Overall, retrograde EVLT presents a valuable option for managing CVI, particularly in patients with anatomical complexities or vasospasm, contributing to improved patient care and outcomes.